Orientation Program for Beginners and Parents - Borgen, William A. (Canadian Journal of Counselling and Psychotherapy, 2012)
A school orientation program was developed to: (a) create a positive base forhome-school communication, (b) provide parents with some information related toschool entry skills, and (c) provide an initial positive school experience for beginningstudents. The program consisted of six meetings, three experiential and threediscussion. During the experiential meetings pre-beginning students were asked toperform everyday activities which demanded use of co-ordination, language, orperception skills. These were selected to suggest to parents the importance ofinteraction with their children in skill development. Topics for the three discussionmeetings involved development of responsible behaviour in children, availability ofpsychological support services through the school, and school rules. The success ofthe program was indicated by parent response to a questionnaire and excellent parentattendance in the schools where it has been used.